2019
DOI: 10.1055/a-0917-4604
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Virtual Reality Training with Upper Limb Sensory Exercise Stimulation on the AROM of Upper Limb Joints, Function, and Concentration in Chronic Stroke Patients

Abstract: Objective We investigated the effect of upper limb sensory stimulation and virtual reality rehabilitation (SMVR) on upper extremity active joint angle, function and cognitive ability in chronic stroke patients. Methods A total of 30 patients were randomly divided into SMVR group and CON group. SMVR group was performed 60 min three times a week for 8 weeks in upper limb sensory stimulation and robot virtual reali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Sample sizes ranged from 18 to 145, for a total of 894 patients with stroke. In total, 11 (47.8%) of the 23 trials were conducted in Korea [34,38,[42][43][44][45][46][47][48][49][50], 3 (13%) in Portugal [51][52][53], 2 (8.7%) in Spain [54,55], 2 in China [36,37], 2 in Australia [56,57], and 1 (4.3%) each in Lithuania [58], Brazil [59] and Turkey [60].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample sizes ranged from 18 to 145, for a total of 894 patients with stroke. In total, 11 (47.8%) of the 23 trials were conducted in Korea [34,38,[42][43][44][45][46][47][48][49][50], 3 (13%) in Portugal [51][52][53], 2 (8.7%) in Spain [54,55], 2 in China [36,37], 2 in Australia [56,57], and 1 (4.3%) each in Lithuania [58], Brazil [59] and Turkey [60].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Regarding the types of VR-based therapies, 16 (69.6%) trials administered VR as a singular session [36][37][38]44,45,[47][48][49]51,52,[54][55][56][57]59,60], 5 (21.7%) trials were categorized as having used VR-based therapies plus occupational therapy [43,46,50,53,58], and 2 trials as having used VR-based therapies plus computer-assisted cognitive rehabilitation [34,42]. The frequency and duration of VR exposure varied considerably between trials.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The oculogyration allowing the eye moving slowly is the movement of eyeball at the speed of less than 100 ° per second, which controls the moving speed and time of the eyeball through a feedback mechanism of the vestibular system and visual system [33]. Kim et al [34] reported that visual virtual reality exercise help improve concentration. Keller et al [18] reported that this oculogyration leads to a significant improvement in body orientation; they also suggested that the activation of the vestibular and visual systems occurs through the oculogyration of the subject, and that the balance ability in standing position is improved.…”
Section: Discussionmentioning
confidence: 99%
“…Methods used to improve balance and gait of stroke patients include training using functional electrical stimulation [ 8 ], dual task exercise [ 9 ], therapeutic approach through collaborative action of Brunstrom [ 10 ], virtual environment rehabilitation [ 11 ], mirror therapy [ 12 ], and so on. Among them, mirror therapy is one of treatments for patients with brain lesions based on the theory of neuroplasticity in the brain.…”
Section: Introductionmentioning
confidence: 99%